Apply analytical procedures in the audit of financial statements - Omanov Sanjar Kurbanazar o’gli (International Consortium of Education and Culture Research Studies, 2020)
This article investigates major points of the applied analytical procedures in the audit of financial statements. On this case, research has pinpointed from different methodological and theoretical points. Therefore, it makes outcomes and shows shortcomings as the major features of the financial statements.